Factors that contribute to the internationalization of SMEs in Johor Bahru / Nordalilah Radzuan - Radzuan, Nordalilah (Faculty of Business and Management, 2015)
The aim of this study was to identify and assess the factors that contribute to the Small Medium Enterprises (SMEs) internationalization in Johor Bahru by various industries that located and operates in Johor Bahru. There are several factors that contribute to the internationalization of SME in Johor Bahru which are Entrepreneurial factor, Firm factor and Environmental factor. The aim of the research is to achieve the research objective which is to identify the most significant factors that contribute to the internationalization of SMEs in Johor Bahru. The factors that contribute to the internationalization of SME had been discussed in several researchers by other researcher. This descriptive study is to know the relationship between all variables and to identify the most significant factors that contribute to the internationalization of SMEs in specific area which is in Johor Bahru. In this research, the sample would be all the SMEs which have 30 industries. And the research is conducted in area Johor Bahru by using convenience sampling. The basis of the research is based on Internationalization theory develop by Antoncic and Hisrich (2000) which is Entrepreneurial, Firm and Environmental Factor.